2001
DOI: 10.1029/2000gl011814
|View full text |Cite
|
Sign up to set email alerts
|

ENSO and eddies on the southwest coast of Mexico

Abstract: TOPEX/POSEIDON and ERS‐2 (T/ERS) sea surface height altimeter observations and the Naval Research Laboratory Layered Ocean Model (NLOM) are used to study the circulation along the southwest coast of Mexico. The results of this research indicate that strong El Niño/Southern Oscillation (ENSO) warm phase Kelvin waves (KW) destabilize the upper ocean circulation. The effect of ENSO appears as three distinct stages. First, a coastal jet characterized by strong vertical shear flow develops. Second, the shear flow s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 9 publications
2
47
0
3
Order By: Relevance
“…Most likely the generation is driven by flow separation at the headlands of the West African coast, triggered by seasonality in the wind forcing. For the northeastern Pacific it has been shown that coastal trapped waves have an impact on the stability of coastal currents and hence eddy generation (Zamudio et al, 2001(Zamudio et al, , 2006(Zamudio et al, , 2007. Such eddy generation mechanisms may explain the high eddy generation in the TANWA found during phases of strongest boundary current velocities.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Most likely the generation is driven by flow separation at the headlands of the West African coast, triggered by seasonality in the wind forcing. For the northeastern Pacific it has been shown that coastal trapped waves have an impact on the stability of coastal currents and hence eddy generation (Zamudio et al, 2001(Zamudio et al, , 2006(Zamudio et al, , 2007. Such eddy generation mechanisms may explain the high eddy generation in the TANWA found during phases of strongest boundary current velocities.…”
Section: Discussionmentioning
confidence: 95%
“…Different mechanisms for the generation of eddies in eastern boundary upwelling regions have been proposed (e.g., Liang et al, 2012). Barotropic and baroclinic instabilities of the near-coastal currents (Pantoja et al, 2012) triggered by, e.g., the passage of poleward propagating coastal trapped waves (Zamudio et al, 2001(Zamudio et al, , 2007, wind perturbations (Pares-Sierra et al, 1993), or interactions of the large-scale circulation with the bottom topography (Kurian et al, 2011) are the main processes identified for the eddy generation in eastern boundary upwelling regions. In the TANWA, the period of maximum eddy generation (June/July) is characterized by a strong near-surface boundary current, the MC (Lázaro et al, 2005) suggesting dynamic instabilities of the boundary current as an important generation mechanism.…”
Section: Seasonal Variability Of Eddy Generationmentioning
confidence: 99%
“…Umatani & Yamagata (1991), as well as Zamudio, Leonardi, Meyers & O'Brien (2001), showed that eddies can be generated even when the wind forcing is almost negligible. One question to consider is if the eddies can be obtained neglecting the wind forcing.…”
Section: Ocean Eddiesmentioning
confidence: 99%
“…They suggested that changes in eddy activity were likely generated by more strong wintertime cold surges into Central America during El Niñ o, but also noted that changes in the background sea level and the passage of strong coastally trapped Kelvin waves associated with ENSO could also modulate eddy activity. Zamudio et al (2001) found that during strong El Niñ o events, a narrow current associated with a downwelling Kelvin wave develops, which becomes unstable and breaks forming anticyclonic eddies that propagate away from the coast at ;188N. Anticyclonic eddies, with a deeper thermocline, were also more prevalent and stronger in the vicinity of Tehuantepec during the 1997 El Niñ o than during the 1998 and 1999 La Niñ a events, where the modulation in eddy generation was again linked to coastally trapped waves that were generated in the equatorial Pacific (Zamudio et al 2006).…”
mentioning
confidence: 99%